Electron trapping of laser-induced carriers in Er-doped SnO2 thin films - Morais, E. A.; Scalvi, Luis Vicente de Andrade [UNESP] (Elsevier B.V., 2007)
In order to investigate optically excited electronic transport in Er-doped SnO2, thin films are excited with the fourth harmonic of an Nd:YAG laser (266nm) at low temperature, yielding conductivity decay when the illumination is removed. Inspection of these electrical characteristics aims knowledge for electroluminescent devices operation. Based on a proposed model where trapping defects present thermally activated cross section, the capture barrier is evaluated as 140, 108, 100 and 148 meV for doped SnO2, thin films with 0.0, 0.05, 0. 10 and 4.0 at% of Er, respectively. The undoped film has vacancy levels as dominating, whereas for doped films. there are two distinct trapping centers: Er3+ substitutional at Sn lattice sites and Er3+ located at grain boundary. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: tin dioxide films; sol-gel; erbium doping